The impact of serum cytokines in the development of early allograft dysfunction in living donor liver transplantation. Issue 16 (April 2018) - Chae, Min Suk; Kim, Jong-Woan; Chung, Hyun Sik; Park, Chul Soo; Lee, Jaemin; Choi, Jong Ho; Hong, Sang Hyun
Abstract : Abstract: Early allograft dysfunction (EAD) is considered a precursor to graft loss in liver transplantation. To date, the use of preoperative serum cytokine profiles to predict EAD development has not been systematically investigated in living donor liver transplantation (LDLT). Here, we investigated the association between preoperative serum cytokine profiles and EAD development in LDLT patients. Serum cytokine profiles collected preoperatively and on postoperative day 7 were retrospectively reviewed. The specific serum cytokines analyzed included interleukin (IL)-2, IL-6, IL-10, IL-12, IL-17, interferon (IFN)-γ, and tumor necrosis factor (TNF)-α. The cytokine levels of patients with EAD were compared with those of patients without EAD and the impact of cytokine levels on the occurrence of EAD was evaluated. Preoperatively, the serum levels of IL-6, 10, 17, and TNF-α were significantly higher in the EAD group than in the non-EAD group. In univariate logistic analysis, the preoperative levels of IL-6, IL-10, IL-17, IFN-γ, and TNF-α were potentially associated with EAD development. After multivariate logistic analysis, higher preoperative serum levels of IL-6 and 17 were significantly associated with EAD development. In addition, the incidence of EAD increased as the preoperative serum levels of IL-6 and IL-17 increased. Preoperative serum levels of IL-6 and IL-17 were significantly associated with EAD development in LDLT.